HIV Clade-C Infection and Cognitive Impairment, Fatigue, Depression, and Quality of Life in Early-Stage Infection in Northern Indians. (July 2016) - Cook, R.; Jones, D. L.; Nehra, R.; Kumar, A. M.; Prabhakar, S.; Waldrop-Valverde, D.; Sharma, S.; Kumar, M.
HIV disease progression is associated with declining quality of life and overall health status, although most research in this domain has been conducted among Western populations where B is the infecting clade. This study sought to determine the effects of early-stage clade-C HIV infection (CD4 count ≥400 cells/mm 3 ) on neurocognitive functioning, cognitive depression, and fatigue by comparing a matched sample of HIV-positive and HIV-negative Northern Indians. This study also examined the impact of these factors on quality of life within the HIV-positive individuals. HIV-positive participants demonstrated reduced cognitive functioning, increased fatigue, and lower quality of life. Fatigue and cognitive impairment interacted to negatively impact quality of life. Results suggest that early-stage HIV clade-C-infected individuals may experience subclinical symptoms, and further research is needed to explore the benefit of therapeutic interventions to ensure optimal clinical outcomes and maintain quality of life in this vulnerable population.